PENGARUH DEBT TO EQUITY RATIO, FREE CASH FLOW, UKURANPERUSAHAAN TERHADAP PEMBAGIAN DEVIDEN(STUDI EMPIRIS PERUSAHAAN FOOD AND BEVERAGES 2010-2014) - PRADITA P . P, PUTU (Jurnal Akuntansi AKUNESA, 2017)
This study uses a quantitative approach for reviewing and re-verify existingtheories. For this type of research itself is causal research, where the researchwas conducted to determine the relationship between the independent variable onthe dependent variable. This research requires secondary data such as financialstatements have been audited and posted by the company. In this study, the objectof the research is that companies food and beverage that have gone public arelisted in the Indonesia Stock Exchange (BEI). Keywords: Dividend, Debt to Equity Ratio, Free Cash Flow, Firm Size